Ptosis: a rare presentation of ocular cysticercosis - Labh, RK; Sharma, AK (Nepalese Journal of Ophthalmology, 2013)
Background: Cysticercosis is a common parasitic infection involving multiple systems and caused by Cysticercus cellulosae, the larval form of the cestode, Taenia solium. The humans become infected by ingesting its eggs from contaminated food. Here, we present a case of ocular cysticercosis which presented with mild pain, ptosis, inflammation of upper eyelid and slightly restricted ocular motility. Case: A twelve-year-old girl presented with mild pain, unilateral ptosis and inflammation of the right upper eyelid for seven months. There was no history of diurnal variation and trauma. There was neither protrusion of the eyeball nor any mass was palpable in periorbital area. Visual acuity in both the eyes was normal. Periocular and ocular examination revealed a slightly restricted ocular motility in the right upward gaze and a reduced vertical fissure height a with good levator palpebrae function. The Bell’s phenomenon was good. The magnetic resonance imaging of the orbit showed an intra-conal retro-orbital mass involving the superior rectus muscle of the right eye suggestive of ocular cysticercosis. The orbital sonogram revealed a cystic lesion in the superior rectus muscle with an echogenic intramural nodule. The enzyme-linked immunosorbent assay for serum antibodies against the cysticercus was positive. The ptosis improved with a therapeutic trial of albendazole and oral steroids for 6 weeks. Conclusion: Extra-ocular cysticercosis can be treated with oral steroid and albendazole. Nepal J Ophthalmol 2013; 5(9):133-135 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7842